A reconstrução da história da Cabanagem em Lealdade, de Márcio Souza e da guerra civil em Moçambique, em As duas sombras do rio, de João Paulo Borges Coelho - Barros, Liliane Batista (Olho d’água, 2015)
Pretendemos analisar a revisitação histórica da guerra civil em Moçambique e da Cabanagem no Brasil nos romances As duas sombras do rio de João Paulo Borges Coelho e Lealdade, de Márcio Souza. Verificaremos como as memórias são articuladas nas duas produções e a contribuição desta para a revisão histórica de fatos que se encontravam esquecidos. This work aims a comparative analysis by revisiting historical facts of Civil Wars of both Mozambique and Cabanagem in Brazil, displayed in the novels As duas sombras do rio, by João Paulo Borges Coelho, and Lealdade, by Márcio Souza. The premises of this research is based on the attention given to the literary setting; and how the authors cover the remembrances in their works, and in which way they add to the historical review of the facts forgotten.